Angiofibroma of Soft Tissue: A Clinicopathological Study of Eight Cases With Emphasis on the Diagnostic Utility of Fluorescence In Situ Hybridization Detection for NCOA2 Rearrangement - Wang, Canming; Fan, Yuqian; Wei, Jianguo; Xu, Qiujie; Ru, Guoqing; Zhao, Ming (Frontiers in Oncology, 2022)
Background: Angiofibroma of soft tissue (AFST) is a rare mesenchymal neoplasm of fibroblastic differentiation. Due to its diverse morphology and the lack of specific immunohistochemistry (IHC) markers, AFST could elicit a broad range of differential diagnosis. Several studies have disclosed in AFST recurrent gene fusions involving NCOA2, mainly AHRR-NCOA2 fusion, providing a useful approach to diagnosing this lesion. We report eight additional cases of this rare entity with emphasis on the diagnostic utility of fluorescence in-situ hybridization (FISH) detection for NCOA2 rearrangement. Methods: Clinicopathological data for eight AFSTs were retrieved. IHC was performed, and FISH was used to detect rearrangements involving NCOA2, DDIT3, and FUS loci. Results: There were 5 female and 3 male patients, ranging in age from 29 to 69 years (median: 55 years). The patients presented mostly with a slow-growing mass in the extremities, with or without intermittent pain. All tumors were located in the lower extremities with 3 ( 27.5%) involving or adjacent to the knee joints. Tumor size ranged from 1.5 to 3.8 cm (median: 3.0 cm). Morphologically, the tumors consisted of a proliferation of uniform, bland spindle cells set in alternating myxoid and collagenous stroma with a prominent vascular network composed of countless small, branching, thin-walled blood vessels. Foci of “chicken wire”-like capillaries, and medium- to large-sized blood vessels with prominent staghorn morphology were evident in 2 and 4 cases, respectively. In addition, sheets of small round cells and foci of cystic changes were observed in 1 each case, Degenerative nuclear atypia was identified in 3 cases, while mitosis and tumor necrosis were absent. By IHC, the stromal cells were variably positive for epithelial membrane antigen, desmin, and CD68. By FISH analysis, 7/8 cases (87.5%) showed NCOA2 rearrangement, and the remaining one had increased gene copy numbers of intact NCOA2; rearrangements involving FUS (0/4) and DDIT3 (0/3) were not identified in the cases analyzed. All tumors were surgically removed and none had recurrence at follow-up from 5 to 73 months. Conclusions: FISH analysis for NCOA2 rearrangement represents a practical method for confirming the diagnosis of AFST on the basis of appropriate histomorphological backgrounds.